Peripheral arterial disease and the diabetic foot syndrome: neuropathy makes the difference!: a narrative review - Rümenapf, Gerhard; Abilmona, Nour; Morbach, Stephan; Sigl, Martin (Journal of Clinical Medicine, 2024)
Background: In vascular medicine, peripheral arterial disease (PAD) and diabetic foot syndrome (DFS) are often considered synonymous with respect to the need for revascularization. In PAD patients, clinical symptoms reflect the degree of atherosclerotic disease, since peripheral innervation, including pain sensation, is not usually compromised. In DFS patients, however, symptoms of relevant foot ischemia are often absent and progression of ischemia goes unnoticed owing to diabetic polyneuropathy, the loss of nociception being the main trigger for foot ulcers. This review analyzes the fundamental differences between PAD and DFS against the background of polyneuropathy. Methods: The literature research for the 2014 revision of the German evidence-based S3-PAD-guidelines was extended to 2023. Results: Vascular examination is imperative for both, PAD and DFS. Stage-dependent revascularization is of utmost importance in PAD patients, especially those suffering from critical limb-threatening ischemia (CLTI). Successful therapy of DFS goes further, including infection and metabolic control, wound management, offloading the foot and lifelong prophylaxis in the course of a multidisciplinary treatment concept. Revascularization is not needed in all cases of DFS. Conclusions: There are fundamental differences between PAD and DFS with respect to pathophysiology, the anatomical distribution of arterial occlusive processes, the clinical symptoms, the value of diagnostic tools such as the ankle-brachial index, and classification. Also, therapeutic concepts differ substantially between the two patient populations.